Strategic Management of Organic Farming Innovation Villages: Enhancing Agricultural Productivity and Sustainability - Ningrum, Dhea Pramestya; Pertiwi, Vidya Imanuari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study addresses the persistent challenge of declining agricultural productivity and environmental degradation caused by conventional, chemical-based farming practices. The main objective is to analyze how strategic management can strengthen the implementation of Organic Farming Innovation Villages (Desa Inovasi Tani Organik, DITO) to improve productivity and sustainability in the agricultural sector. Employing a qualitative case study design, the research involved purposively selected informants, including government officials, agricultural extension workers, and members of farmer groups. Data were collected through in-depth interviews, observations, and documentation, validated using triangulation, and analyzed using the interactive model of Miles and Huberman. Findings were interpreted through Wheelen and Hunger’s strategic management framework, covering environmental scanning, strategy formulation, implementation, and evaluation. Results indicate that fertile land, strong farmer institutions, and policy support act as key strengths, while weaknesses include limited extension personnel and entrenched reliance on conventional methods. Opportunities are driven by growing consumer demand for healthy products and regulatory support, whereas threats include climate variability, land degradation, and farmer resistance. Implementation has shown positive impacts through training, mentoring, demonstration plots, and organic certification, though challenges remain in human resource capacity, fertilizer production, and market stability.